Metformin Attenuates Renal Fibrosis in a Mouse Model of Adenine-Induced Renal Injury Through Inhibiting TGF-β1 Signaling Pathways - Yi, Hao; Huang, Chunling; Shi, Ying; Cao, Qinghua; Chen, Jason; Chen, Xin-Ming; Pollock, Carol A. (Frontiers in Cell and Developmental Biology, 2021)
It is well recognized that all progressive chronic kidney disease (CKD) is pathologically characterised by ttubulointerstitial fibrosis process. As inflammatory and fibrotic signaling pathways play central roles in the progression of CKD regardless of aetiology, targeting inflammatory and fibrotic responses are logical strategies to limit renal fibrosis. Metformin has been used as a first-line therapy to lower blood glucose in patients with type 2 diabetes mellitus (T2DM) for over 50 years. Accumulating evidence suggests the potential for additional therapeutic applications of metformin, including mitigation of renal fibrosis. However, the mechanisms whereby metformin limits adenine-induced renal injury are not reported. In this study, the anti-fibrotic effects of metformin independent of its glucose-lowering mechanism were examined in an adenine -induced mouse model of CKD. Adenine induced CKD was associated with increased expression of inflammatory markers MCP-1, F4/80 and ICAM, fibrosis markers type IV collagen and fibronectin, and TGF-β1 compared to control groups, which were partially attenuated by metformin treatment. The results also suggest that metformin reduced inflammatory and fibrotic responses through Smad3, ERK1/2 and P38 pathways. These results suggest that metformin attenuates adenine-induced renal interstitial fibrogenesis through inhibition of TGF-β1 signaling pathways, independent of its glucose-lowering action.